Counselling the Elderly and their Carers - Terry, Paul (Macmillan Education UK, 1997)
Taking a psychodynamic approach, Counselling the Elderly and their Carers draws on psychoanalytical ideas and their application to individuals, groups, institutions and society, providing a unique insight into the increasingly important area of working with the elderly and their carers. Focusing on understanding the unconscious as well as the conscious experience of being elderly and frail, it addresses issues such as retirement, deteriorating physical illness and death. The importance of the carer is recognised in this book, and includes accounts of working with individual staff in their role as keyworkers for particular patients - work which sheds light on the care-giving relationship, its rewards and frustrations, as well as on how abusive practices may develop between carer and patient. There is a description of working with carers in a support group; working with managers of a long-stay hospital; and of meetings between elderly patients and staff on long-stay wards. This book is aimed at readers who wish to be introduced to the theory and practice of counselling and psychotherapy in this area. It will appeal to a wide range of professionals, including counsellors, therapists, nurses, social workers, doctors and geriatricians, and will prove invaluable to both qualified professionals and students
Keywords: Geriatric Care; Nursing; Psychotherapy and Counseling; Geriatric nursing; Applied psychology